EXPOSICAO DE CIRURGIOES-DENTISTAS AO MERCURIO - Larini, L.; Salgado, P. E T (My University, 1981)
The professional exposure of dental surgeons to mercury has attracted a great deal of attention from governmental organs and institutions in different countries. Considering that the normal ratio is 10 μg/1000 ml of urine, it was verified from tests that 72.7% of the professionals working in the dental practice in the city of Araraquara (SP) Brazil, show mercury levels above this limit. These results demonstrated the almost complete unawareness of many dentists to mercury and, consequently, precautionary measures were almost nonexistent.
Exposure of dental surgeons to mercury
Keywords: mercury; brazil; dentist; drug toxicity; drug urine level; human; human experiment; inhalational drug administration; intoxication; normal human; occupational exposure; oral drug administration; urine